2019
DOI: 10.20473/jaki.v7i2.2019.147-154
|View full text |Cite
|
Sign up to set email alerts
|

Urban-Rural Disparity: The Utilization of Primary Healthcare Centers Among Elderly in East Java, Indonesia

Abstract: Background: Urban always attracts investors to invest. Health facilities in urban areas are growing rapidly compared to villages. This condition is estimated to contribute to the disparity of urban-rural areas in the utilization of health services. Studying the utilization of health services is a way to evaluate the performance of the health care system through its output.Aim: This study analyzed the urban-rural disparity in the utilization of primary healthcare center by the elderly.Method: This study used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
1
24
0
1
Order By: Relevance
“…Age is closely related to a person's risk factors for illness. The older you are, the greater the risk for getting sick, especially degenerative diseases (Laksono, Nantabah and Wulandari, 2018;Wulandari and Laksono, 2019), including accidents (Kanters et al, 2020). Similar findings are also informed in several previous studies in various countries which concluded that the older a person is, the higher the risk of experiencing illness (Ma et al, 2020;Jaramillo and Willging, 2021;Wang et al, 2021).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Age is closely related to a person's risk factors for illness. The older you are, the greater the risk for getting sick, especially degenerative diseases (Laksono, Nantabah and Wulandari, 2018;Wulandari and Laksono, 2019), including accidents (Kanters et al, 2020). Similar findings are also informed in several previous studies in various countries which concluded that the older a person is, the higher the risk of experiencing illness (Ma et al, 2020;Jaramillo and Willging, 2021;Wang et al, 2021).…”
Section: Resultssupporting
confidence: 74%
“…Increased health insurance membership is carried out through the National Health Insurance Program with the segment of participants who are paid wage workers, non-wage workers, non-workers, and Contribution Aid Recipients (Erlangga, Ali and Bloor, 2019). Contribution Aid Recipients who are a group of poor people can participate in the National Health Insurance with a premium paid by the government (Wulandari et al, 2019;Wulandari, Putri and Laksono, 2020). However, various challenges still have to be faced to achieve total coverage, especially for those who do not receive contribution assistance (Suharmiati, Laksono and Astuti, 2013;Idris, Satriawan and Trisnantoro, 2017;Sari and Idris, 2019;Suparmi, Iram Barida Maisya, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Urban areas in Indonesia tend to be the focus of development. This has an impact on growth in urban areas which is faster than rural, including development in the health sector (Wulandari and Laksono, 2019). The difference in input and output in the health sector between these two areas should also be a concern of policymakers in the health sector because their job is to ensure equitable access for all people in need (Mubasyiroh, Nurhotimah and Laksono, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Distributing and placing an adequate number of quality health workers in disadvantaged areas significantly increases the level of equal health services. Indonesia still displays a substantial disparity between urban and rural areas (Wulandari and Laksono, 2019), as well as between the respective regions, districts, and provinces in the country (Laksono, Wulandari, and Soedirham, 2019). Data from the Board for Development and Empowerment of Human Resources in Public Health in 2019 explained that the distribution of health workers can be derived from the ratio of doctors in parts of Jakarta Province with 65 doctors per 100,000 people, while West Java and Banten have 11 doctors per 100,000 citizens.…”
Section: Original Researchmentioning
confidence: 99%